A NOVEL RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE QUANTIFICATION OF A POTENTIAL ANTI-DIABETIC DRUG METFORMIN HYDROCHLORIDE IN TABLET DOSAGE FORM - HIREMATH, JAYASHREE A.; KUMAR, HARISH (International Journal of Current Pharmaceutical Research, 2022)
Objective: This study was conducted to develop a simple, economical, linear, rapid method for the assay studies of Metformin HCl by RP-HPLC method and to carry out the method validation. Methods: A simple, robust and accurate method to carryout assay of Metformin hydrochloride tablet(500 mg) by RP-HPLC method in which the stationary phase used is Shimadzu shim-pack GIST C18 column with specification (5μm×4.6×250 mm). This method involves isocratic elution of mobile phase containing 70% buffer and 30% acetonitrile. The buffer used for analysis is Tetra-Butyl Ammonium Hydroxide (0.002%), the flow rate was maintained at 0.5 ml/min. detection was done at 232 nm. Principal peak for Metformin was observed at 3.5 min and the runtime for each injection was set to 10 min. The standard solutions of Metformin were prepared using purified water (milli-Q water) and scanned from 190 nm to 400 nm. Sharp peaks were observed in the range of 232 nm and thus, wavelength of 232 nm was selected and used throughout the validation process. Results: Linearity graph generated was found acceptable and accurate and the graph was generated in the range of 50% to 150% concentration. The regression coefficient was found to be 0.999(acceptable range). Validation was carried out according to ICH guidelines and found to be acceptable. Conclusion: This developed method was found to be simple, robust, economical, accurate, linear and can be used in the assay of Metformin tablet using RP-HPLC.